Students’ Mathematical Literacy Based on Self-Esteem By Brain Based Learning With Trigo-Fun E-Module - Zakkia, Agustin; Isnarto, Isnarto; Sri Noor Asih, Tri (Unnes Journal of Mathematics Education Research, 2021)
This study aims to describe the ability of mathematical literacy based on the mathematical self-esteem of class X students. This type of research is a mixed method. The design of this study is sequential explanatory. The population in this study was class X SMA Negeri 1 Slawi consisting of ten classes. The sampling technique using purposive sampling and selected class X.10 as an experimental class. Determination of the subject grouped by self-esteem with high, medium, and low categories to be interviewed about students' mathematical literacy abilities. The results showed that learning the description of mathematical literacy ability in terms of students' self-esteem varied. This is shown from 4 students with high self-esteem obtained by mathematics literacy results in the form of 2 students in the high category and 1 student in the medium category. From 27 students with moderate self-esteem, mathematics literacy results were obtained in the form of 7 students in the high category, 14 students in the moderate category, and 6 students in the low category. From 4 students with low self-esteem mathematical literacy results in the form of 1 student in the high category and 3 students in the low category.